Tourism geopolitics in the “back of beyond” - Nicolas Savelli (Revue de Géographie Alpine)
The Valgaudemar valley, in the French department of Hautes-Alpes, is an exception in the tourism landscape of the Alps in that it does not have a ski resort. In this isolated valley, whose “back of beyond” location has made it marginal both geographically and economically, it was decided to base territorial development on a “re-anchoring” process that strengthened local ties with the surrounding high mountains. Taking a slightly different approach and working with a network of actors from the mountain activities sector should make it possible for “outsiders”, the small, less conventional operators, to find their place in the tourism market. Geographic independence, once identified as a handicap, now seems, on the contrary, to be a generator of innovation through collective intelligence, thanks to the scope for action that the area enjoys through its independence of any established model of tourism development.